Broadening Participation by Including More Individuals With Disabilities in STEM: Promising Practices from an Engineering Research Center. (May 2018) - Bellman, Scott; Burgstahler, Sheryl; Chudler, Eric H.
This article describes successful practices for including individuals with disabilities (e.g., leaders, students, faculty researchers, advisory board members) in the Center for Sensorimotor Neural Engineering (CSNE), an Engineering Research Center funded by the National Science Foundation. The methods, tools, and materials presented in this article can be used by others seeking to increase the inclusion of individuals with disabilities in postsecondary science, technology, engineering, and mathematics (STEM) programs. Methods are employed to ensure that the CSNE is welcoming and accessible to individuals with a wide range of abilities and to recruit individuals with disabilities into significant roles that support the Center's mission. These efforts have resulted in the engagement of individuals with disabilities in the Center's operations, activities, and research at a higher rate when compared with all Engineering Research Centers.